Sensor based on semiconductor nanostructures for polycyclic aromatic hydrocarbons detection in water objects - Sushko, O. A.; Rozhitskii, M. M. (ISE, 2013)
Every year in the world's water basins fall thousands of chemicals with unpredictable effects, many of them are hazardous for human being among which are polycyclic aromatic hydrocarbons (PAHs). That is why their detection and content monitoring are quite important Modern methods and means for the determination of PAH have several disadvantages such as high detection limit, low selectivity, long duration and complexity of the analysis procedure. The work sensor based on semiconductor nanostructures avoiding of these disadvantages is described.
Keywords: sensor; semiconductor nanostructures; polycyclic aromatic hydrocarbons